“The Million-Euro Answer”: Party Youth Wings’ Views on the Opportunities and Challenges of Political Communication on Social Media - Sara Machado; Vasco Ribeiro; Raquel Meneses (Media&Jornalismo)
Research on the relationship between youth, politics, and social media often overlooks the role and views of party youth wings. In this study, we seek to fill this gap by understanding (1) the objectives guiding the political communication of party youth wings on social media and (2) the opportunities and challenges they identify in the process. We do so by conducting semi-structured interviews with representatives of youth wings and informal youth groups from Portuguese political parties. Information emerges as the primary communicational objective of youth wings, who do not consider social media an ideal space for political dialogue. Although social media is the main communication channel with young people, offering more reach, flexibility, and feedback opportunities, several challenges limit the effectiveness of communication: resources, algorithms, audience fragmentation, selection effects, simplification of complexity, and the irreplaceability of face-to-face contact. The implications of these results are discussed.